A atividade seguradora no Brasil e sua relação comercial com os resseguradores internacionais - León, Gustavo Amado (2019)
This master essay aimsto review the commercial relationshipsamong Brazilianinsurance marketand the international reinsurance companies,focusing to provide an analysis andcritical reflectionon the basis of each discussed contract, the insurance and reinsurance. Therefore, it was adopted a line of reasoning that facilitates the understanding of the project with a brief presentation of creation and formation of the insurance contract, its different definitions by national and foreign experts, as well as its main internal structures, such as elements, characteristics and guiding principles. In fact, the insurance contract is a legal and economic business, making it fundamental in this text to systematically relate the study of insurance, beyond Law, within the domains of Economics, with emphasis on the Brazilian. In a secondmoment, reference is made to reinsurance, whichis not an unique instrument, but a relationship that can be implemented under innumerous distinguish forms. Additionally, it is not an inert and immutable instrument, presenting individual development in course of time, especiallywhen it is related to its types. In the same way that it was presented the insurance contract, this project reviews the mains important aspects of the reinsurance contract, mainly its creation history, its elements, definitions and importance in relation to the international economy. Therefore, after understanding how the legal-economic guidelines of insurance and reinsurance contracts work, this text comes up with a conclusion in relation to problem of negotiations between insurance companies and reinsurance companies, in their international relationship,also incorporating some questions that are in vogue actually to the insurance and reinsurance markets in Brazil, with the possibility to admit that an excessively intervention of the Brazilian insurance regulator by its own regulations can cause a barrier to develop the economy and the commercial trades among national and internationalagents; the attribution of rules and regulatory impositions by different kind of normative statements which inhibit the entrance of new layers in the Brazilian insurance market; the economic objective of the insurance and reinsurance markets; the problem of bureaucratizationof the regulated companies activities and the maintenance of the foreigner companies inside the Brazilian reinsurance market, which highly influence the future of the markets. Finally, it is concluded with animportant point to be questioned which is the way the Brazilian regulator can interfere in the development of economic andcommercial markets, which means that the Public Administrationcan influence the commercial and economic markets between insurance and reinsurance companies